A qualitative exploration of how pharmacy professionals in primary care utilise planned protected development time - Fiona Cairns; Robyn Patrick; Gillian Calderhead; Paul Forsyth; Gazala Akram (Elsevier, 2024)
Background: With patients developing more complex healthcare and medicine needs, it is imperative pharmacy professionals enhance their knowledge and skills to enable an advanced level of pharmaceutical practice, improving service provision and supporting patient care. The UK Royal Pharmaceutical Society (RPS) is urging employers to incorporate protected time within the working week to facilitate this development. Currently protected development time (PDT) is not well established within the pharmacy profession and there is little qualitative data available about the utility of this. Objective: To explore how pharmacy professionals in primary care currently utilise planned protected 'development time' and their perception of this. Methods: One-to-one semi-structured interviews were conducted between February and March 2023 via Microsoft Teams® with pharmacists, pharmacy technicians (PTs) and pharmacy support workers (PSWs), working in a large Health board area in Scotland who had established PDT since August 2021. Interview recordings were transcribed verbatim and analysed using an inductive thematic framework approach. Results: Interviews were conducted with 13 participants (12 female); 6 pharmacists, 5 PTs and 2 PSWs. Five core themes were derived from the data: logistics, competing priorities, methods for development, inequalities and benefits. Participants utility of PDT was variable, most focused on self-development to improve clinical knowledge however, supporting the development of others often taking precedence. Disparities in utility and inequity of protection from service delivery were highlighted. All participants befitted from PDT reporting a self-assessed improvement in confidence and competence. Conclusion: The experience of participants who had PDT was typically perceived as positive including supporting development and improving wellbeing however, it fostered inequalities which needs addressing. Educational input is required to provide direction for development across all four pillars of professional practice; clinical practice, leadership, education and research, promoting advanced practice. Further research is required to assess the impact of PDT on health outcomes of the local population.